Strategies for public management reform - Jones, Lawrence; Schedler, Kuno; Mussari, Riccardo (Research in public policy analysis and management, 2004)
This book is unique in that it explores public sector reform from a strategic management perspective. The authors whose work is represented in the book examine seven strategies for public management reform: (1) increases in accountability, (2) decentralization and delegation of authority and responsibility for decision making and management, (3) application of information technology to improve management and responsiveness of governments to citizens, (4) developing and improving management control systems in the public sector, (5) measures to reduce corruption in government, business and society, (6) development and use of performance indicators, and (7) integration of performance measurement and management in public organizations. Authors address the need for and application of various strategies, and impediments to implementation of each strategy. Case analysis is used to derive findings and conclusions.